PERAN UNITED NATIONS WOMEN (UN WOMEN) DALAM PENANGGULANGAN EKSPLOITASI SEKSUAL DAN PERDAGANGAN PEREMPUAN MIGRAN DI YUNANI - Fransiska GP Purba; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research focuses on the role of UN Women in helping its member states, in this case Greece, to eradicate transnational crimes of sexual exploitation and human trafficking that are mainly targetting women. Greece is one of the European Country that face human trafficking case, which victims are mainly come from Balkans, East Europe, Asia, and Africa. The purpose of this research is to understand how international organization as independent actor contributes to solve an international phenomenon that involves non state actor from outside Greece.In analysing the case study, this research applies the theory of role and function of international organizations and the systemic level of analysis to understand the influence of international system to international actor’s behaviors. The datas are collected by using explanatory qualitative methodology in order to gain a deeper analysis and understanding. Most of the datas are published by UN Women and other UN organizations, Hellenic Police, and annual report from independent organization.The result of this research showed that UN Women’s contribution in helping Greece in combatting sexual exploitation and migrant women trafficking was through assisting legal drafting, providing capacity building, and ensuring coordination between state and NGO along with the Greece government and society, without any further intervention in the implementation process. All of the programme above are made by focusing on CEDAW (Convention of Elimination of All Forms of Discrimination Against Women), Beijing Platform for Action, and another sustainable programme, that will help in the process of law making and amend according to Greece’s condition and needs.  Key Words: International Organization, UN Women, Human Trafficking, Migrant Women, Sexual Exploitation.